Soil characteristics of wet sand under different impulse polarity and earth electrode's dimensions - Nor, N.; Ramli, A. (IEEE-INST ELECTRICAL ELECTRONICS ENGINEERS INC, 2008)
Soil characteristics under high impulse currents for soil with various moisture contents have been well studied in previous work. The effects of impulse polarity, soil grain size and the earth electrode's dimensions on soil characteristics under high impulse conditions were investigated. In the study, the hemispherical test cell was used, and the parallel plate was adopted for the study of the effects of earth electrode's dimensions. This however may not provide a direct comparison for the earth electrode's dimensions, since the hemispherical test cell has the non-uniform electric field distribution, whereas the parallel plate has a uniform electric field distribution. Due to that, this present paper is to provide the effect of the same configuration i. e. cylindrical test cell, but with different earth electrode's dimensions. The effect of impulse polarities was also studied.